Description of Albuminuria Levels in Patients with Type 2 Diabetes Mellitus According to Length of Diagnosis at West Nusa Tenggara Provincial Hospital - Ika Nurfajri Mentari; Bustanul Atfal; Aini Aini (Postgraduate, University of Mataram, 2023)
Albuminuria is a condition in which there is albumin in the urine, albuminuria often occurs in patients with type 2 DM which occurs due to persistently elevated blood sugar levels and poor glycemic control. This will risk the occurrence of complications of them diabetic nephropathy but it takes about 5-10 years after the diagnosis of DM is established to become a significant problem of kidney damage. The purpose of this study was to find out how the description of albuminuria levels in patients with type 2 DM based on the duration of diagnosis at RSUP NTB. The method used was analytic observation with a cross sectional design. The results of this study analyzed 30 subjects, consisting of 14 men (47%) and 16 women (53%) with an age range of 30-71 years, with the prevalence of urine albumin levels based on the duration of being diagnosed with type 2 diabetes, which is â‰¤ 5 years. DM â‰¥ 5 years with a prevalence of 3 (10%) samples having normoalbuminuria levels, 18 (60%) samples having micro albuminuria levels, and 3 (10%) samples having macro albuminuria levels